Per studiare il vocabolario del passato: la posizione delle parole in epoca storica - Burgassi, Cosimo; Guadagnini, Elisa (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2023)
This paper aims to propose a new method for describing the lexicon of a language in a specific period of its history. The first paragraph outlines the two main ideas to be found in the studies concerning both synchronic and diachronic lexicology. In the second paragraph our method for lexical inquiry is presented together with its core concepts, which are textual Corpus Representativeness, Connotation, Connotation Rate (Quoziente Connotativo, QC) and word Position in the Center-Periphery Vocabulary Model. The third paragraph sketches two possible research lines, the first one regarding the lexicon of a given historical period (Old Italian), the second dealing with the comparison between two different linguistic historical phases (Old Italian vs. Contemporary Italian).